Optimization of Vertical Axis Wind Turbine Systems to Capture Vehicle-Induced Highway Winds - Aydin Ulus; Stefan Ilie Moldovan (Energies)
This study introduces an innovative set of guide vanes that increase the efficiency of Vertical Axis Wind Turbines (VAWT) using winds generated by vehicles traveling on highways. The increase in efficiency is based on enhancing the airflow interaction as the vehicle moves past the turbine. Initial Computational Fluid Dynamics (CFD) simulations with two guide vanes setups demonstrated a 56.81% increase in power output under wind generated by passenger vehicles. Further design enhancements, incorporating three guide vanes with optimized geometries, led to a 242% improvement in power generation. Additional simulations evaluated the performance under wind conditions generated by larger vehicles, such as buses. The three guide vanes configuration yielded a 102% increase in energy capture efficiency in these scenarios. The findings suggest that vehicle-induced winds—typically an untapped energy source—can be effectively harvested using tailored turbine system designs. By integrating passive flow control strategies such as guide vanes, VAWTs can operate more efficiently in highway environments. This research highlights a novel pathway for enhancing renewable energy systems and supports broader efforts toward sustainable energy development through the utilization of unconventional wind sources. This performance enhancement is primarily due to the aerodynamic redirection of airflow toward the advancing blade and away from the returning blade, reducing drag and improving torque generation.